77.2k views
0 votes
What is the answer? ​

What is the answer? ​-example-1
User Shabbir
by
5.2k points

2 Answers

4 votes

Explanation:

Side AB and Side BC are the same so we can make them equal to each other:

3x -4 = 5x -10

Subtract 3x from both sides.

-4 = 2x -10

Add 10 to both sides.

6 = 2x

Divide both sides by 2

3 = x

x = 3

Now substitute x in the expression

3x -4

3(3) -4

PEMDAS

9 - 4

Subtract

5

User Pavel Hasala
by
4.9k points
2 votes

Answer:

Required Answer:-

  • If
    \triangle ABC is a isosceles triangle then
  • AB=BC

Now Substitute values


\longrightarrow
\sf 3x-4=5x-10


\longrightarrow
\sf 5x-10=3x-4


\longrightarrow
\sf 5x-3x=-4+10


\longrightarrow
\sf 2x=6


\longrightarrow
\sf x={\frac {6}{2}}


\longrightarrow
\sf x=3


\therefore
\sf AB=3x-4=3* 3-4=9-4 \\ \sf AB=5units

User Liju Mathew
by
4.5k points